O uso do Geogebra como recurso tecnológico didático para modelagem gráfica da função quadrática - BRABO, Eveny Thamires Beckman (2022)
This Course Conclusion Paper investigates the use of the Geogebra application as a pedagogical practice for teaching and learning quadratic function content. To this end, it aimed to analyze the advantages for teaching mathematics with the insertion of the Geogebra application for teaching graphical modeling of the quadratic function. The methodology used in this research was the field study with emphasis on a qualitative approach for the purpose of gathering more consistent information about teaching mathematics. It was carried out in a class of the first year of High School, in a state school in the city of Vigia de Nazaré-Pa. The methodology used in this research was the field study with emphasis on a qualitative approach for the purpose of gathering more consistent information on the teaching of Mathematics. The results point to an increasing trend in the use of new technologies, software and applications, as didactic resources used to assist in the teaching of various areas of knowledge, especially Mathematics.